2019
DOI: 10.3389/fnins.2019.01109
|View full text |Cite
|
Sign up to set email alerts
|

Fornix Stimulation Induces Metabolic Activity and Dopaminergic Response in the Nucleus Accumbens

Abstract: The Papez circuit, including the fornix white matter bundle, is a well-known neural network that is involved in multiple limbic functions such as memory and emotional expression. We previously reported a large-animal study of deep brain stimulation (DBS) in the fornix that found stimulation-induced hemodynamic responses in both the medial limbic and corticolimbic circuits on functional resonance imaging (fMRI) and evoked dopamine responses in the nucleus accumbens (NAc), as measured by fast-scan cyclic voltamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…For example, ELSM was reported to alter fatty acid metabolism in isolated skeletal muscle, along with exogenous free fatty acid (FFA) oxidation, exogenous FFA incorporation into intracellular triacylglycerol (TG), and intracellular TG content in the isolated muscle fibers [ 52 ]. ELSM was also reported to increase glucose metabolism in neurons detected by micro-PET imaging of FDG uptake [ 53 ]. Global analysis of the transcriptome and proteome demonstrated that ELSM significantly regulated proteins and genes enriched in biological processes related to glycolytic pathways, fatty acid oxidation, oxidative phosphorylation, as well as autophagy/mitophagy and oxidative stress, in human myotubes [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, ELSM was reported to alter fatty acid metabolism in isolated skeletal muscle, along with exogenous free fatty acid (FFA) oxidation, exogenous FFA incorporation into intracellular triacylglycerol (TG), and intracellular TG content in the isolated muscle fibers [ 52 ]. ELSM was also reported to increase glucose metabolism in neurons detected by micro-PET imaging of FDG uptake [ 53 ]. Global analysis of the transcriptome and proteome demonstrated that ELSM significantly regulated proteins and genes enriched in biological processes related to glycolytic pathways, fatty acid oxidation, oxidative phosphorylation, as well as autophagy/mitophagy and oxidative stress, in human myotubes [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Improvement of glycometabolism by fornix DBS also has been indicated. Positron emission tomography (PET) revealed that 30 minutes of fornix DBS in normal rats increased glucose metabolism, which was mostly noted in limbic circuits including the hippocampus, papilla, anteromedial thalamus and ipsilateral NAc 72 . Furthermore, 5 of 6 AD patients in a Phase I trial accepted PET examination after 1 year of fornix DBS, which showed that the glucose metabolism in the cortico‐thalamic and cortico‐hippocampal network was increased 73 .…”
Section: Treatment Effects Of Fornix Dbs In Admentioning
confidence: 99%
“…Positron emission tomography (PET) revealed that 30 minutes of fornix DBS in normal rats increased glucose metabolism, which was mostly noted in limbic circuits including the hippocampus, papilla, anteromedial thalamus and ipsilateral NAc. 72 Furthermore, 5 of 6 AD patients in a Phase I trial accepted PET examination after 1 year of fornix DBS, which showed that the glucose metabolism in the cortico-thalamic and corticohippocampal network was increased. 73 In a Phase II trial, PET showed that fornix DBS had increased glucose metabolism in the temporal and parietal lobe at the 6th month, but the change was insignificant in the 12th month.…”
Section: Stimulation Parameters and Strategy Of Fornix Dbs In Admentioning
confidence: 99%
“…FSCV possesses some features that are better suited to quantitatively measure changes in extracellular neurotransmitter concentrations in chronic or behavioral studies, including fewer equipment needs relative to other techniques and implantation versatility. , Additionally, the typical carbon fiber microelectrode used with FSCV is smaller (7 μm in diameter, 50–150 μm in length), thus providing micrometer spatial resolution of detection in tissue with less damage. FSCV also benefits from a subsecond temporal response and low limits of detection (e.g., <5 nM) for serotonin, though techniques like microdialysis have significantly lower limits. Like microdialysis, FSCV has also been applied to several animal-based disease models and is well-established within their respective fields. However, a noteworthy drawback to FSCV is that because conventional FSCV requires background subtraction of tonic redox currents, it has been limited to the measurement of neurochemical phasic changes induced by relatively brief bouts of chemical or electrical stimulation of neuronal elements in tissue. Thus, the requirement for background subtraction can only provide relative changes to the concentration of the analyte, not their absolute value.…”
Section: Serotonin Measurement Techniquesmentioning
confidence: 99%